Implementasi Promosi Sekolah di SDI Technopreneur An Nadwah - Sihabudin Sihabudin; Siti Qomariyah; Muhammad Helmi Alfian; U. Ruhimatullah; Deliyanti Dimyati (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to describe the implementation of school promotion at SDI Technopreneur An Nadwah as an effort to increase the interest of prospective new students. The research employs a descriptive qualitative method with data collection techniques including observation, informal interviews, and document analysis. The results show that the basic concept of SDI Technopreneur An Nadwah is based on the national curriculum integrated with technopreneurship programs, tahfiz, and the cultivation of Islamic character habits. The promotional strategies used include publication through social media, school branding programs, collaboration with PAUD/TK institutions, open house activities, and the distribution of printed media. Promotional implementation is carried out in a structured manner through the creation of digital content, the organization of public events, and the provision of digital-based PPDB (new student admission) information services. The obstacles encountered include limited promotional human resources, content consistency, and competition among schools; however, these can be addressed through the formation of a dedicated promotion team, strengthening the school’s flagship content, and optimizing digital media. This study concludes that effective school promotion can enhance institutional visibility and attract the interest of prospective new students more optimally.